2009
DOI: 10.1158/1078-0432.ccr-09-0090
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis Targeting Tumor Microenvironment Synergizes Glucuronide Prodrug Antitumor Activity

Abstract: Purpose: This study is aimed at investigating the in vivo antitumor activity of a novel cellimpermeable glucuronide prodrug, 9-aminocamptothecin glucuronide (9ACG), and elucidating the synergistically antitumor effects of antiangiogenesis therapy by targeting the tumor microenvironment. Experimental Design:We analyzed the antitumor effects of 9ACG alone or combined with antiangiogenic monoclonal antibody DC101on human tumor xenografts by measuring tumor growth and mouse survival in BALB/c nu/nu nude and NOD/SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 43 publications
1
45
0
2
Order By: Relevance
“…bG is considered as a tumor marker (14,15,20) and a prodrug-activating enzyme for cancer prodrug therapies (35,36). Connors and Whisson demonstrated that high bG levels present in plasmacytomas were correlated with higher drug sensitivity of the tumors (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…bG is considered as a tumor marker (14,15,20) and a prodrug-activating enzyme for cancer prodrug therapies (35,36). Connors and Whisson demonstrated that high bG levels present in plasmacytomas were correlated with higher drug sensitivity of the tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…9-11) and gene-directed enzyme prodrug therapy (GDEPT; refs. 6, 12, 13) as well as directly in prodrug monotherapy, which relies on the elevated levels of bG found in the tumor microenvironment (14)(15)(16) to selectively convert prodrug into active drug. For instance, Albin and colleagues reported that the level of bG human breast tumors was up to 6-times greater than that in normal tissues (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Juan and colleagues (29) demonstrated that antiangiogenic agents can synergize the antitumor activity of glucuronide prodrugs by selectively enhancing concentration of the activating enzyme in the tumor microenvironment. More recently, the concept of glucuronidase-responsive albumin-binding prodrugs seemed to represent a promising approach to limiting the rapid renal clearance observed with previous glucuronide prodrugs (46).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have shown that glucuronide prodrugs can be activated by b-glucuronidase present in high concentrations in necrotic areas of most solid tumors, including glioblastomas (27). b-Glucuronidase is secreted extracellularly in tumors by inflammatory cells such as neutrophils and macrophages, while in healthy tissues, its activity is confined to lysosomes (28,29). This enzymatic specificity of the tumor microenvironment allows glucuronide prodrugs to discriminate between malignant and normal tissues.…”
Section: Introductionmentioning
confidence: 99%